The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.orglett.0c03131
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Access to Azetidine-Based α-Amino Acids and Applications to Small Peptide Synthesis

Abstract: Non-natural azetidine-based amino acids (Aze) present interesting features in protein engineering. A simple organometallic route toward unsaturated carboxylic acid precursors is presented. Subsequent metal-catalyzed asymmetric reduction allowed for the synthesis of a new library of 2-azetidinylcarboxylic acids, which were finally employed in the formation of small peptide chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Most of these compounds proved to be stable and allowed for establishing a new library of functionalized building blocks (Scheme 30). [80] Further asymmetric syn ‐reduction of the double bond employing a ruthenium complex in the presence of a BINAP‐type ligand led to the desired aze derivatives 48 in good yields and reasonable enantiomeric ratios (up to 94 : 6).…”
Section: Further Applications Of Unsaturated Four‐membered Ringsmentioning
confidence: 99%
“…Most of these compounds proved to be stable and allowed for establishing a new library of functionalized building blocks (Scheme 30). [80] Further asymmetric syn ‐reduction of the double bond employing a ruthenium complex in the presence of a BINAP‐type ligand led to the desired aze derivatives 48 in good yields and reasonable enantiomeric ratios (up to 94 : 6).…”
Section: Further Applications Of Unsaturated Four‐membered Ringsmentioning
confidence: 99%
“…[7] The molecular structure of 2-azetines, on the other hand, has been discussed based on limited examples: Barluenga et al reported the structure of azetinylcarbene compound I, [8] and Didier and co-workers succeeded in the isolation and characterization of II as a unique cyclic amino acid (Figure 1b). [9] Synthetic studies of 2-azetines have encompassed investigations into intermolecular [2 + 2] cycloaddition processes. Kobayashi and co-workers reported [2 + 2] cycloaddition reactions of imines and alkynyl sulfides in the presence of lanthanide triflate [Ln(OTf) 3 ] or BF 3 •OEt 2 catalyst (Scheme 1, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, we recently contributed to this field through manipulation of unsaturated analogs – 2 H -azetines – via Diels–Alder cycloadditions or hydrogenation reactions. 7…”
mentioning
confidence: 99%